1980
DOI: 10.1063/1.440319
|View full text |Cite
|
Sign up to set email alerts
|

Potential energy and dipole moment surfaces for simultaneous torsion and pyramidalization of ethylene in its lowest-lying singlet excited states: A CI study of the sudden polarization effect

Abstract: A b initio CI calculations have been carried out in a double-zeta AO basis for the simultaneous torsion and pyramidalization energy and dipole moment surfaces of the two lowest (V and Z) singlet excited states of ethylene. In nonpyramidalized geometries these two electronic states are found to undergo a potential crossing for a twisting angle of ϑ=82 °, with the Z(1A1) species being the more stable for the perpendicular D2d conformation. The dipole moments of these states are found to increase quite rapidly wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
2

Year Published

1985
1985
2004
2004

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 23 publications
5
46
0
2
Order By: Relevance
“…As expected, 9,10,14,17,18 the crossing ͑or near degeneracy͒ of the V state with the Z state at near-perpendicular geometry of ethene is reached by a fast spreading of the torsional wave packet on a time scale of the order of 10 fs. A new result of paper I and the present work is the finding that the antisymmetric scissors is the essential coupling mode for the V -Z conical intersection.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As expected, 9,10,14,17,18 the crossing ͑or near degeneracy͒ of the V state with the Z state at near-perpendicular geometry of ethene is reached by a fast spreading of the torsional wave packet on a time scale of the order of 10 fs. A new result of paper I and the present work is the finding that the antisymmetric scissors is the essential coupling mode for the V -Z conical intersection.…”
Section: Discussionmentioning
confidence: 69%
“…7 and 8 and the references therein. The first accurate calculations of the torsional PE functions of the three valence electronic states N ͑for normal, that is, ground state͒, V ͑for valence͒, and Z ͑for zwitterionic͒ have been performed with the MRD-CI method by Buenker et al 9 and Persico and Bonacić-Koutecký. 10 The so-called sudden-polarization effect, arising from the near degeneracy of V and Z in 90°t wisted ethene, has been investigated in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a calculation in which C',, symmetry is imposed for r , = r2 gives rise to discontinuity problems, as already mentioned in the previous section and also as encountered by Gillispie et al in their NO' study (2). The problem of the variation of CI results on the choice of the one-electron basis for close-lying electronic states has been previously discussed in a CI study of the sudden polarization effect (23,24). Figures 2-4 show that the crossing seam in the 'A' surfaces is located near 107" for all chosen distances, but that the energy of the crossing goes up considerably when going to smaller bond distances.…”
Section: Results Of the Calculationsmentioning
confidence: 87%
“…Several configuration interaction (CI) studies on ethylene have shown that at (near) perpendicular geometries three important singlet states arise: the N state, which is the (CR) ground state at this geometry, and the ionic Z and V states, which become degenerate at a central bond twist angle of about 80°. 9,12 In the vicinity of this degeneracy, lowering of the nuclear symmetry by pyramidalizing one of the carbon centers leads to the formation of considerable dipole moments in the Z and V states of ethylene.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of both experimental 27,28,34,38,42,43,48,51,52,56 and theoretical 3,9,12,15,23,[58][59][60] studies have been performed in an attempt to gain both experimental evidence and additional information about the driving forces governing this symmetry breaking, which is often referred to as sudden polarization, 4 especially in the condensed phase.…”
Section: Introductionmentioning
confidence: 99%